Levels of Information Needs as Perceived by Women Culinary Entrepreneurs in Depok Municipality, Indonesia - Said, Mashadi; Anggraeni, Diana; Febrina, Diah (Advances in Social Sciences Research Journal, 2018)
Culinary business has become a business choice for a high number of women in the area of Depok Municipality, Indonesia. This research is aimed at finding out the levels of information needs of women culinary entrepreneurs in undertaking their business processes based on five categories of the types of information, including product, product development, training, marketing, and finance. Data on the levels of information needs under the five categories of the types of information were obtained from 96 women culinary entrepreneurs through a survey. The result of the research reveals that out of the five categories of the types of information fully needed by women culinary entrepreneurs, the 'product' and 'training' information occupies the highest position, at 86.5% of the total responses, followed by marketing information (81.2%), financial information (80.2%), and product development information (77.1%). It implies that women culinary entrepreneurs, especially in Depok Municipality, strongly need various types of information related to their culinary business. Therefore, the related agency, particularly the government, need to take strategic measures to provide information required by women culinary entrepreneurs in Depok Municipality in particular and in Indonesia in general.